The molecular mechanism underlying pathogenicity inhibition by sanguinarine in Magnaporthe oryzae. Issue 10 (24th June 2021) - Anjago, Wilfred Mabeche; Zeng, Wenlong; Chen, Yixiao; Wang, Yupeng; Biregeya, Jules; Li, Yunxi; Zhang, Tian; Peng, Minghui; Cai, Yan; Shi, Mingyue; Wang, Baohua; Zhang, Dongmei; et al.
Abstract: BACKGROUND: Sanguinarine (SAN) is a benzophenanthridine alkaloid that broadly targets a range of pathways in mammalian and fungal cells. In this study we set out to explore the molecular mechanism of sanguinarine inhibition of the fungal development and pathogenicity of Magnaporthe oryzae with the hope that sanguinarine will bolster the development of antiblast agents. RESULTS: We found that the fungus exhibited a significant reduction in vegetative growth and hyphal melanization while the spores produced long germ tubes on the artificial hydrophobic surface characteristic of a defect in thigmotropic sensing when exposed to 4, 8 and 0.5 μm sanguinarine, respectively. Consistent with these findings, we observed that the genes involved in melanin biosynthesis and the fungal hydrophobin MoMPG1 were remarkably suppressed in mycelia treated with 8 μm sanguinarine. Additionally, sanguinarine inhibited appressorium formation at a dose of 1.0 μm and this defect was restored by supplementing 5 mM of exogenous cAMP. By qRT‐PCR assay we found cAMP pathway signalling genes such as MoCAP1 and MoCpkA were significantly repressed whereas MoCDTF1 and MoSOM1 were upregulated in sanguinarine‐treated strains. Furthermore, we showed that sanguinarine does not selectively inhibit vegetative growth and appressorium formation of Guy11 but also other strains of M. oryzae . Finally, treatment of sanguinarine impaired the appressorium‐mediated penetration and pathogenicity of M. oryzae in a dose‐dependent manner. CONCLUSION: Based on our results we concluded that sanguinarine is an attractive antimicrobial candidate for fungicide development in the control of rice blast disease. © 2021 Society of Chemical Industry. Abstract : We found that sanguinarine inhibits developmental stages such as fungal growth, hyphal melanization and appressorium‐mediated penetration in a dose‐dependent manner.